The practice of unit testing by five software development companies in Malaysia - Hussain, Marzilah (2002)
Software testing is regarded as the most important and the most crucial of the final stages in software development. Profound knowledge and experience in software testing is often an asset in a software company to ensure the reliability and quality of any developed project. The core of software testing strategies mainly lies with unit testing, which is a type of testing carried out on single subroutine or module, almost throughout the development process, depending on the development model used by the developer. There are some issues raised in software testing literature, be it in textbooks, journals, or articles, regarding the process of unit testing, its importance, and the problems faced by developers in performing unit tests. However, through the research and readings of the author on the literature, these issues have not been formally discussed in a Malaysian perspective. Hence, this study of the unit testing practice of software development companies operating in Malaysia is carried out. After reviewing the current available literature on unit testing with no specific geographical or time frame limitation, a study is carried out on five software development companies, within the geographical limit of Malaysia and as of the current time, on their engaged practice of unit testing. It is meant to gauge the importance they place in unit testing, as well as to find out their methods, their processes, and the problems they encounter in unit testing. These findings are then analyzed and compared to the current literature. It is hoped that these case studies will shed more light on the real-world practice of software development, especially of unit testing, in a Malaysian context.